2004
DOI: 10.1038/sj.bjc.6601950
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and practices of patients with advanced cancer: implications for communication

Abstract: The aim of this study was to investigate the beliefs that patients with advanced cancer held about the curability of their cancer, their use of alternatives to conventional medical treatment, and their need to have control over decisions about treatment. Of 149 patients who fulfilled the criteria for participation and completed a self-administered questionnaire, 45 patients (31%) believed their cancer was incurable, 61 (42%) were uncertain and 39 (27%) believed their cancer was curable. The index of need for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…53,64 Even when discussions are held, a truthful assessment of their prognosis is often not given. 65,66 Although physician estimates of prognosis are more accurate than patient estimates, 67,68 physicians often communicate an overly optimistic prognosis, or only provide vague statements without a specific time estimate, even in patients who express a desire to hear the truth. 65,66 Patients often do not understand common statistical terms or manipulate them to make them more positive.…”
Section: Communicating Prognosismentioning
confidence: 97%
“…53,64 Even when discussions are held, a truthful assessment of their prognosis is often not given. 65,66 Although physician estimates of prognosis are more accurate than patient estimates, 67,68 physicians often communicate an overly optimistic prognosis, or only provide vague statements without a specific time estimate, even in patients who express a desire to hear the truth. 65,66 Patients often do not understand common statistical terms or manipulate them to make them more positive.…”
Section: Communicating Prognosismentioning
confidence: 97%
“…Second, health-care providers may have provided the required information, but the patients do not recall having received this material. Patients may avoid such information to help maintain a sense of hope (Leydon, 2000;Beadle et al, 2004). Another explanation may include deficits in health-care providers' training and education, system time and related financial restrictions or competing priorities.…”
Section: The Needs Of Patients With Advanced Incurable Cancermentioning
confidence: 99%
“…10 Other studies have demonstrated high rates of confusion in advanced cancer patients as to whether their cancer is curable or incurable. 11,12 There are also high rates of discordance between patients and their families, with one Australian survey finding in over a third of those with incurable cancer only one of the patient-carer pair understood that their treatment was not intended to cure. 13 Patient-physician disparity regarding understanding of prognosis may be due to a range of factors (Table 1).…”
Section: Introductionmentioning
confidence: 99%